2022
DOI: 10.3390/pharmaceutics14061222
|View full text |Cite
|
Sign up to set email alerts
|

Active Potential of Bacterial Cellulose-Based Wound Dressing: Analysis of Its Potential for Dermal Lesion Treatment

Abstract: The use of innate products for the fast and efficient promotion of healing process has been one of the biomedical sector’s main bets for lesion treatment modernization process. The aim of this study was to develop and characterize bacterial cellulose-based (BC) wound dressings incorporated with green and red propolis extract (2 to 4%) and the active compounds p-coumaric acid and biochanin A (8 to 16 mg). The characterization of the nine developed samples (one control and eight active wound dressings) evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Recently, propolis has been used as an active component in wound biomaterials for its antimicrobial effects, but to the best of our knowledge, the antibiofilm, antiinflammatory, and cell proliferative activities of chitosan-BPE films have not been evaluated [23,24,[37][38][39][40][41][42]. When formulated in corn-starch-based wound dressing with hyaluronic acid, the proliferation of mouse fibroblasts was observed, but this was due to Human keratinocytes (NCTC 2544) produce a high basal level of ROS; stimulation with BPE reduced in a dose-dependent manner the production of radicals (Figure 15B).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, propolis has been used as an active component in wound biomaterials for its antimicrobial effects, but to the best of our knowledge, the antibiofilm, antiinflammatory, and cell proliferative activities of chitosan-BPE films have not been evaluated [23,24,[37][38][39][40][41][42]. When formulated in corn-starch-based wound dressing with hyaluronic acid, the proliferation of mouse fibroblasts was observed, but this was due to Human keratinocytes (NCTC 2544) produce a high basal level of ROS; stimulation with BPE reduced in a dose-dependent manner the production of radicals (Figure 15B).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, records in the literature have been demonstrating the bioactive potential of this resin [7]. Among the examples of bioactivity of this matrix are the antioxidant, antimicrobial, anti-inflammatory, antiparasitic, antiviral, and antitumor actions [8][9][10][11]. In their studies, Silveira et al [12] showed that the antiviral action of green propolis was promising in the treatment of patients with COVID-19, reducing hospitalization time and the development of kidney damage (a common sequela in patients with the disease).…”
Section: Introductionmentioning
confidence: 99%